The use of gamification strategies to encourage user engagement and cloth recycling behaviour - Azhar, Norhafizah; Che Din, Sharkawi (Universiti Teknologi MARA, Perak, 2025)
This research investigates how gamification strategies can enhance user engagement and encourage cloth recycling behaviour in Malaysia. With textile waste reaching alarming levels at 432,901 metric tonnes recorded in 2021, there is an urgent need for creative and sustainable solutions. Employing a mixed-methods approach, the research integrates a systematic literature review with a quantitative survey conducted with 50 participants aged between 18 to 65. The results indicate a high level of awareness and previous involvement in cloth recycling, with significant barriers including limited access to recycling facilities and a lack of information about recycling activities. Respondents expressed a strong interest in gamified recycling initiatives, particularly in features such as points, rewards and community engagement. Incentives were identified as the most effective motivator, with 72% of participants saying they would be more inclined to recycle when rewards are offered. The research finding indicates that user-centric gamification systems that are well-designed can turn recycling into an engaging activity, bridging the gap between awareness and consistent action. These insights provide valuable guidance for policymakers, app developers, educators and advocates of sustainability who seek to encourage long-term recycling behaviours and support environmental goals.